SOSIALISASI PEMBERDAYAAN GENERASI MILENIAL TERHADAP PERKOPERASIAN DI ERA INDUSTRI 4.0 PADA MAHASISWA UNIVERSITAS PEMBINAAN MASYARAKAT INDONESIA - Reza Ichsan; Sarman Sinaga; Nazla Rachma Panggabean; Venny Fraya Hartin Nst (Jurnal PKM Hablum Minannas, 2022)
This community service is carried out online, which is attended by students from the Indonesian Community Development University, the Implementation Method is used by means of Lectures, discussions and questions and answers about empowering the millennial generation of Cooperatives in the Industrial 4.0 era, by understanding the importance of cooperatives in economic development in Indonesia, especially the city of Medan The Let's Cooperative Movement is a momentum to raise the spirit of cooperatives among the younger generation by using technology as a medium for developing cooperatives in the city of Medan, this activity is also very enthusiastic to be followed because the empowerment of cooperatives provides solutions to improve welfare.